A QUALITATIVE APPROACH OF THE TRADE UNION AND ITS REATION WITH THE EMPLOYEES PERFORMANCE IN PT. MEARES SOPUTAN MINING - Rimbing, Richard (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Mostly the large companies in Indonesia even the world have workers who joined in trade union. The general purpose of trade union is to fight, defend, or protect the rights of the workers. The goal of this research is to explore the relation between trade union and employees’ performance in company. The research informants are 11 persons, some of them are members of trade union and the rest didn’t join the union. This research uses qualitative method by interview, case study approach and exploratory design. This research is conducted in PT. Meares Soputan Mining. The result shows that the employee performance; Employees’ Motivation, Job Knowledge, and Employees’ Discipline. The management of the company and leaders of trade union must conduct intense evaluation meetings, in order to know and respond about employees’ condition in the field.   Keywords: Trade Union, Employee Performance